FALSE ADVERTISING PRACTICE IN RESIDENTIAL PROPERTY BILLBOARD? AN EMPIRICAL EVIDENCE - Kiky, Andreas (ULTIMA Management, 2024)
bstract-This study examines the practice of false advertising in residential property advertisements in the Jakarta and Tangerang areas. Developers use advertisements presenting information on distance and travel time to attract potential buyers. This research aims to detect whether the information presented in these advertisements matches the actual conditions on the ground. This research provides the first empirical evidence of inaccurate ads and false advertising practices in the property business in Jakarta and Tangerang Regency. Data was collected from 41 physical advertisement samples spread across the study area. The analysis results show that the advertised distance and travel time are shorter and faster than actual measurements using Google Maps. Statistical tests using paired t-tests indicate significant differences between the advertised information and the exact conditions. The paired t-test is significant at a 1% level of significance. Regulators must address the existence of false advertising in property business. Providing inaccurate or doubtful information can harm the long-term reputation of the developers themselves. Future research can address a cause-effect model to understand the consumer behavior behind their purchase decisions. Because property assets can act as investment assets, the behavioral intention and rational expectation about future property prices are also worth investigating. Keywords: False Advertising; Business Ethics; Billboard Ads; Residential Property; Property Management